Language vitality of kensiu : issues of intergenerational language transmission, language use, and language attitude - Mohd Hilmi Hamzah,; Muhammad Hafiz Ummah Abu Bakar Bakri,; Hasliza Abdul Halim, (Penerbit Universiti Kebangsaan Malaysia, 2024)
The present study reports the language vitality of Kensiu, an endangered Austroasitic language spoken by less than 300 individuals in Kampung Orang Asli Lubuk Legong in the northern state of Kedah, Malaysia. Following UNESCO’s language vitality assessment, this study aims to explore three critical issues related to language vitality: (1) intergenerational language transmissions; (2) language use; and (3) language attitude. Data were collected at the Kensiu settlement through semi-structured interviews involving two male native speakers representing younger and older generations of Kensiu. The data were analysed qualitatively using ATLAS-Ti version 8 and were interpreted via assessment tools such as UNESCO’s language vitality assessment and the Extended Graded Intergenerational Disruption Scale (EGIDS). The results reveal some evidence of intergenerational language transmission within the Kensiu community. The language appears to be used in limited domains, such as ‘family’ and ‘friendship’, with the High variety (Malay) being given more emphasis over the Low variety (Kensiu), though there is a balanced relationship between diglossia and bilingualism. The gap in Sustainable Literacy is also apparent in the literary resources related to the Kensiu language. With regard to language attitude, there are some contrasting perspectives between older and younger generations, though both participants generally agree about the identity of Kensiu speakers and the way they accommodate other dominant languages in their daily life. The findings shed some light on the concepts of intergenerational transmission, language use, and language attitude on the Kensiu language and provide an avenue for further investigations involving endangered indigenous languages in Malaysia.